Legume-Derived Anti-Angiogenic Networks Targeting Renal Cell Carcinoma: Mechanistic Insights into Polyphenol–Saponin–Fiber Bioactive Complexes from Phaseolus vulgaris - Barack Ndenga (Publisher, 2025)
Renal cell carcinoma (RCC) remains one of the most angiogenesis-dependent solid tumors, characterized by constitutive activation of hypoxia-inducible signaling and resistance to long-term anti-VEGF therapies. Emerging evidence suggests that complex dietary bioactives may exert multi-targeted anti-neoplastic effects beyond single-molecule pharmacology. Here, i propose and mechanistically explore Phaseolus vulgaris (red kidney bean) as a source of integrated anti-angiogenic bioactive complexes composed of polyphenols,saponins, and fermentable fiber-derived metabolites. I demonstrate that these legume-derived compounds act synergistically to suppress RCC proliferation, disrupt tumor-driven angiogenesis, and reprogram metabolic and inflammatory signaling pathways. This work introduces a novel framework positioning legume bioactives as systems-level modulators of renal oncogenesis, opening avenues for complementary nephro-oncological strategies.
Renal cell carcinoma (RCC) is a highly vascularized malignancy driven by dysregulated hypoxia signaling, metabolic reprogramming, and chronic inflammation. Despite advances in anti-angiogenic therapies, long-term clinical efficacy remains limited by adaptive resistance and cumulative toxicity. This work introduces a novel systems-level framework positioning Phaseolus vulgaris (red kidney bean) as a source of integrated legume-derived bioactive complexes capable of modulating multiple oncogenic networks simultaneously. The manuscript explores the synergistic anti-proliferative and anti-angiogenic roles of polyphenols, saponins, and fiber-derived microbial metabolites, with a specific focus on renal tumor biology. Mechanistic insights highlight the suppression of HIF-driven angiogenesis, inhibition of PI3K/AKT/mTOR signaling, modulation of endothelial function, and activation of AMPK-mediated metabolic control through the gut–kidney–tumor axis By advancing the concept of Legume-Derived Bioactive Complexes (LDBCs) and applying principles of network pharmacology to nephro-oncology, this work bridges molecular oncology, nutritional biochemistry, and systems medicine. The findings support the repositioning of dietary legumes as complementary, low-toxicity modulators of angiogenesis and tumor progression in renal cell carcinoma, with potential translational relevance for integrative and precision oncology strategies.